Cross-border development: A long-term role for Universities - Smith, Robert Brian; Smith, Nucharee Nuchkoom (ASEAN Journal of Community Engagement, 2020)
Low-income economies are experiencing potential serious threats in terms of long-term sustainability and social development. At the same time, most developing economies are grappling with possible disruptions from the Fourth Industrial Revolution and the current COVID-19 pandemic and its economic consequences. However, every economy has the same goal of elevating its status to that of a developed country. This research uses the narrative/case study approach to examine cross-border development and the role that universities can play as important actors in the development of society. Moreover, this research combines observations and literature analysis. Universities are clearly best placed to play an important role in helping the development of a country and assisting less-developed neighboring countries. However, this role will require continuous long-term commitment. In numerous cases, universities must make significant internal changes to meet the challenges posed by the Fourth Industrial Revolution. Three issues are identified as priority areas to be addressed: the quality of higher education, complex government bureaucracies, and ineffective on-the-job training. These issues will require universities to provide high-quality offerings that are relevant to their community and the broad world market. Moreover, universities must improve the foreign language skills of students and staff to enable them to communicate and learn from worldwide developments. Finally, universities should be proactive in creating opportunities rather than reactive and waiting for others to provide them with opportunities.